Another look at devaluation and the trade balance in China - Ethan McGee; Kamal Prasad Upadhyaya; Rabindra N. Bhandari (Review of Economic Analysis (REA), 2020)
This paper estimates the effect of Chinese Yuan devaluation on the trade balance of China. For that a regression equation is developed in which domestic income, foreign income, domestic money supply, foreign money supply and real effective exchange rate are used as explanatory variable with trade balance as the dependent variable. In order to test the J-curve phenomenon the lagged values of exchange rata are also included. Quarterly time series data from 1999 to 2016 are used. Before estimating the model the time series properties of the data are diagnosed and an error correction model is developed and estimated. The estimated results show that the contemporaneous effect of devaluation is positive, but the total effect is insignificant. A J-curve pattern of adjustment of the trade balance is also detected.
Keywords: F10; F31; F32; 330; Devaluation; trade balance; Error correction model; China